Sosialisasi Penggunaan Internet yang Sehat bagi Anak-Anak di yayasan Domyadhu - Wiwi Apriyanti Wiwi; Erni; Muchlas Syahlanisyiam; Yolanda Anggraini; Sahrul Gunawan; Rinawang Tyas Arinanto; Rahnat Adnan Fauzan; Nuryanti Tuto Suban; Asmat; Affandi Agung (Abdi Jurnal Publikasi, 2022)
Community service is an activity that aims to help the community in the form of activities in any form. Community Service Activities are a part of Pamulang University. The author carried out this PKM activity with the title "Socialization Regarding Healthy Internet Use for Children at the Domyadhu Foundation". This activity is carried out to provide knowledge and enthusiasm to children at the Foundation to be able to understand more and not be wrong in using the internet. The methods used in an effort to achieve the targets or goals that have been planned are introduction, practice and question and answer. The activities that have been carried out are evaluated. Based on the service activities that have been carried out, the socialization training that has been carried out at the Foundation has run smoothly as expected. In fact, this activity received a positive response, both from the Foundation and from participants who have participated. The conclusion that the author can take is that the use of a gadget is good or bad, it all depends on a person's awareness in using it.